2003
DOI: 10.1590/s1415-47572003000400007
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-environment interaction and phenotypic stability for girth growth and rubber yield of Hevea clones in São Paulo State, Brazil

Abstract: The best-yielding, best vigour and most stable Hevea clones are identified by growing clones in different environments. However, research on the stability in Hevea brasiliensis (Willd. Adr. ex Juss.) Muell.-Arg. is scarce. The objectives of this work were to assess genotype-environment interaction and determine stable genotypes. Stability analysis were performed on results for girth growth and rubber yield of seven clones from five comparative trials conducted over 10 years (girth growth) and four years (rubbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Gonçalves et al (2009a) found significant effects at 1% probability in a study with progenies at more than one location. The results of test evaluating the genotype can be used to select and recommend clones adapted to a particular agro-climatic condition if the differences can be defined according to environmental factors (Gonçalves et al 2003). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonçalves et al (2009a) found significant effects at 1% probability in a study with progenies at more than one location. The results of test evaluating the genotype can be used to select and recommend clones adapted to a particular agro-climatic condition if the differences can be defined according to environmental factors (Gonçalves et al 2003). …”
Section: Resultsmentioning
confidence: 99%
“…The high coefficient of variation for rubber yield indicates that the experimental data are subject to experimental errors, despite being within the normal standard for rubber tree (Costa et al 2000, Gonçalves et al 2003.…”
mentioning
confidence: 97%
“…MHPRVG*MH value shows the average genotypic value of the progenies in the two sites, and this amount has already been penalized by instability and capitalized by adaptability (Carbonell et al, 2007). Environmental variations can interfere at GxE interactions, thus it is important and necessary to identify stable genotypes that produce well in various conditions (Gonçalves et al, 2003).…”
Section: Productivity Stability and Adaptabilitymentioning
confidence: 99%
“…Results concerning genetic parameter estimates, genotype x environment interaction, mating system and genetic gain predictions were reported in a number of papers (Gonçalves et al, 1992(Gonçalves et al, , 2003Boock et al, 1995;Costa et al, 2000b).…”
Section: Introductionmentioning
confidence: 95%